ANALYSIS OF ACCOUNTING INFORMATION SYSTEM OF VILLAGE FUND USING LUDER CONTINGENCY MODEL - Oman Rusmana; Muhamad Rizki; Roni Budianto; Eko Suyono (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
This study examines the implementation of a village accounting information system by using village aparatus as informen in Karangsalam Kidul, Banyumas, Central Java. This study uses a mix-method between qualitative and qualitative approaches. For the qualitative approach, data were gathered via in-depth interviews and observations, whereas for the quantitative approach, APBDes 2021 documentation was utilized. In addition, this study employs the Luder contingency model to analyze qualitative data. Quantitative research, in contrast, utilized ratio analysis and sensitivity analysis. This study demonstrates that the implementation of a successful accounting information system in the village of Karangsalam Kidul, Banyumas, Central Java, had a positive effect on financial management and reporting.